PROGETTO STREAMING - STRategiE di mitigazione e gestione dei rischi AMbientalI: casi di studio Nel territorio reGionale Toscano Azioni locali di sostenibilità: cinque progetti per il futuro del territorio toscano - Bartalucci, Chiara; Fagioli, Federico; Giachetti, Andrea; NICCOLAI, ALBERTO; Verdi, Leonardo (Proceedings e report, 2022)
The STREAMING project (STRategiE di mitigazione e gestione dei rischi AMbientalI: casi di studio Nel territorio reGionale Toscano) was funded by POR FSE 2014-2020. The project supported five post-doc on five different case studies for the period 2018-2021 at DAGRI, DICEA e DIEF of the University of Florence. This volume represents a handbook on the best practices for sustainable development in Tuscany summarizing the main results from the STREAMING project. Synergies between project results and Sustainable Development Goals for the Tuscany region are included in the volume.